2008
DOI: 10.1038/leu.2008.255
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone marrow microvascular density in haematological malignancies is associated with differential regulation of angiogenic factors

Abstract: Antiangiogenic drugs are currently tested in haematological malignancies. As these drugs target different angiogenic regulators, and as cancers are inherently heterogeneous, a detailed characterization of angiogenesis in individual cancers is needed. Hence, we measured bone marrow microvessel density (MVD), plasma concentrations of eight angiogenesis-related parameters and the expression in blood mononuclear cells of 40 angiogenesis-related mRNAs in 93 patients with haematological neoplasias (acute myeloid leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 42 publications
2
43
0
4
Order By: Relevance
“…The capacity of HIF-1a to regulate VEGFA and IL8 gene expression by MM cells confirmed our previous data, 27,39 and supports HIF-1a as a key regulator of angiogenesis also in MM cells because VEGF 9,10 and at least in part of IL-8 39,40 are well-known factors involved in MM-induced angiogenesis. CCL2 and MMP9 could be also involved in the pro-angiogenic role of HIF-1a, because both cytokines are produced by MM cells and contribute to angiogenesis and BM spreading.…”
Section: Discussionsupporting
confidence: 88%
“…The capacity of HIF-1a to regulate VEGFA and IL8 gene expression by MM cells confirmed our previous data, 27,39 and supports HIF-1a as a key regulator of angiogenesis also in MM cells because VEGF 9,10 and at least in part of IL-8 39,40 are well-known factors involved in MM-induced angiogenesis. CCL2 and MMP9 could be also involved in the pro-angiogenic role of HIF-1a, because both cytokines are produced by MM cells and contribute to angiogenesis and BM spreading.…”
Section: Discussionsupporting
confidence: 88%
“…A total of 1.6×10 4 HUVECs dispersed evenly in medium containing 1% FBS were placed onto the Matrigel layer in each well. The cells were treated with DMSO (0.1%) or various concentrations of QSN-10c (25, 50, 100, and 200 μmol/L).…”
Section: Apoptosis Detection By Flow Cytometrymentioning
confidence: 99%
“…The growth of a tumor mass beyond 2 to 3 mm 3 is often preceded by increased formation of new blood vessels essential for the delivery of nutrients and oxygen as well as the removal of metabolic waste from the tumor microenvironment [1,2] . Moreover, many recent studies have demonstrated the important role of angiogenesis in hematologic neoplasms [3][4][5] . Therefore, anti-angiogenic and angio-prevention therapies represent promising approaches to control tumor growth and metastasis [6,7] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its pro-angiogenic characteristics, IL-8 may be a key mediator in the angiogenesis and progression of various tumors. IL-8 has been revealed to be involved in seminal plasma-induced regulation of vascular function in cervical cancer (20), transition between liver cirrhosis and highly vascularized hepatocellular carcinoma (18), the malignant phenotype of hematological malignancies (38), Epstein-Barr virus latent membrane protein-1-induced angiogenesis in nasopharyngeal carcinoma through the NF-κB-binding site (22) and tumor growth and angiogenesis in melanoma via the secretion of tumor necrosis factor α and IL-1α (21). A previous study has identified that gastric cancer cells secret various levels of IL-8 protein and, more notably, the level of IL-8 mRNA in the neoplasms is markedly associated with vascularization in vivo, suggesting that IL-8 may regulate neovascularization and the growth and spread of gastric cancer (39).…”
Section: Discussionmentioning
confidence: 99%